The Role of Gut Microflora and the Cholinergic Anti-inflammatory Neuroendocrine System in Diabetes Mellitus - Parekh, Parth J.; Nayi, Vipul R.; Johnson, David A.; Vinik, Aaron I. (Frontiers in Endocrinology, 2016)
The obesity epidemic has drastically impacted the state of health care in the United States. Paralleling this epidemic is the incidence of diabetes mellitus, with a notable shift toward a much younger age of onset. While central to the pathogenesis of diabetes associated with obesity is the role of inflammation attributed to “adiposopathy.” Emerging data suggest that changes in sympathetic/parasympathetic balance regulated by the brain precede changes in the inflammatory cascade. It has now been established that the gut microflora contributes significantly to the activation and inhibition of autonomic control and impact the set of the neuroinflammatory inhibitory reflex mediated by the cholinergic nervous system. There has been a paradigm shift toward further investigating commensal bacteria in the pathogenesis of obesity and diabetes mellitus and its complications, as dysbiosis is thought to play a pivotal role in diabetic-associated disorders. This paper is intended to evaluate the role of intestinal dysbiosis in the pathogenesis of diabetes mellitus and examine the potential for restoration of balance via use of probiotics.